Pengaruh Revitalisasi Pasar Tradisional Dan Sumber Daya Pedagang Terhadap Kinerja Pedagang Pasar Di Kota Denpasar - Prathiwa Pradipta, Anak Agung Gede; Nata Wirawan, I Gusti Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 4, April 2016 (pp.385 - 429), 2016)
Revitalization the tradisional market is one of the government’s program to improve the performance of the market traders in Denpasar. The aim of this research was to find out the influence of the traditional market revitalization and the resource merchant to the performance of traders market in Denpasar. This research was done in Denpasar, included ten tradisional markets that have been revitalization. The sample in this research was a hundred participant, it is part of the merchants in ten markets that have been on the revitalization in Denpasar. The method of research that used was a structured interview and observation. This research used two methods analyze, they are konfimatori factor analysis and multiple linear regression analysis. The konfimatori factor analysis was used to get the factor scores of laten variables formed by indicator variables, whereas the regression analysis was used to analyze the influence of the independent variable to the dependent variable. The result of the analysis partially showed the variable market revitalization and resource merchant had a significant effect to the performance of market traders. The variable that dominant influenced to the performance of market traders in Denpasar was variable market revitalization.
Keywords: traditional market, revitalization of markets, resources and performance merchant trader